2010
DOI: 10.1016/j.mrgentox.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase structure-based insight on the mutagenic properties of 8-oxoguanine

Abstract: An aerobic environment burdens DNA polymerase substrates with oxidized substrates (DNA and nucleotide pools). A major promutagenic lesion resulting from oxidative stress is 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxoG). Guanine oxidation alters the hydrogen bonding properties of the base and glycosidic-preference of the nucleotide. The favored glycosidic syn-conformation exposes the Hoogsteen edge of the base for hydrogen bonding with adenine during DNA synthesis. The cell has recognized the threat of this lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 38 publications
1
98
0
Order By: Relevance
“…To this end, we determined binary (pol/DNA) and ternary (pol/DNA/dNTP) X-ray crystal structures of human DNA polymerase β (pol β) with 5ClC in the templating position of a 1-nt-gapped DNA duplex (Table 2). Pol β is a model mammalian DNA polymerase involved in base excision repair and may encounter DNA lesions in the templating strand during repair of the genome (32)(33)(34). The binary DNA complex structure with 5ClC in the templating position diffracted to 2.0 Å.…”
Section: Results 5clc Is a Mutagenic Base That Is Easily Bypassed By mentioning
confidence: 99%
“…To this end, we determined binary (pol/DNA) and ternary (pol/DNA/dNTP) X-ray crystal structures of human DNA polymerase β (pol β) with 5ClC in the templating position of a 1-nt-gapped DNA duplex (Table 2). Pol β is a model mammalian DNA polymerase involved in base excision repair and may encounter DNA lesions in the templating strand during repair of the genome (32)(33)(34). The binary DNA complex structure with 5ClC in the templating position diffracted to 2.0 Å.…”
Section: Results 5clc Is a Mutagenic Base That Is Easily Bypassed By mentioning
confidence: 99%
“…It has been demonstrated that active site flexibility around the template base allows conformational alternation of 8-oxo-G in DNA polymerases with standard active site dimensions (25). This template flexibility allows the syn 8-oxo-G base to form a potent base pair with mismatched anti dATP, causing A misincorporations by virtually all classes of DNA polymerases (2,4,26) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The slight preference of POL ␤ for rCTP over rATP insertion opposite 8-oxodG mirrors a similar small discrimination between dCTP and dATP (27). The major determinant of dual coding by a template 8-oxodG is its ability to assume both syn and anti conformations (27)(28)(29). Our data indicate that this property is not detectably affected by the presence of a C2Ј oxygen and ribonucleotide insertion opposite a template 8-oxodG appears to follow the same rules as deoxyribonucleotide incorporation.…”
Section: Discussionmentioning
confidence: 99%